Anomalous Hall and Nernst Effects in Co2TiSn and Co2Ti0.6 V0.4Sn Heusler Thin Films - Hu, Junfeng; Ernst, Benedikt; Tu, Sa; Kuvezdic, Marko; Hamzic, Amir; Tafra, Emil; Basletic, Mario; Zhang, Youguang; Markou, Anastasios; Felser, Claudia; Fert, Albert; Zhao, Weisheng; et al. (Physical Review Applied, 2018)
Magnetotransport (magnetoresistance and anomalous Hall effect) and thermoelectric (Seebeck and anomalous Nernst effect) effects are investigated on epitaxially grown Co2TiSn and Co2Ti0.6V0.4Sn Heusler thin films. An anomalous Nernst coefficient up to 1.8 μV/K is observed in Co2Ti0.6V0.4Sn at 220 K, which is almost 12 times larger than in the undoped Co2TiSn thin film at 300 K. In analogy to the anomalous Hall angle, we extract the anomalous Nernst angle from experimental results by comparing the anomalous Nernst voltage with the thermopower. The anomalous Nernst angle for Co2Ti0.6V0.4Sn is 15% at 220 K, whereas it is only 0.5% for the undoped film. Considering the Mott relation for anomalous Hall and Nernst effects, these experimental results may be accounted for by an enhanced energy derivative of the anomalous Hall conductivity at the Fermi level that is shifted by vanadium doping. These results of a large anomalous Nernst angle provide opportunities to realize spin-caloritronic devices for efficient on-chip energy harvesting based on magnetic Heusler thin films.
CRIS-Team Scopus Importer:2022-04-14